Synthesis, Characterization of Chitosan-ZnO/CuO Nanoparticles Film, and its Effect as an Antibacterial Agent of Escherichia coli - Ahmad Fatoni; Agnes Rendowati; Lasmaryna Sirumapea; Lidya Miranti; Siti Masitoh; Nurlisa Hidayati (Science and Technology Indonesia, 2023)
The film of chitosan- ZnO/CuO nanoparticles was synthesized. This study were the synthesis and characterization of the chitosan-ZnO/CuO nanoparticles film and its effect as an antibacterial of Escherichia coli. The ZnO, CuO, and ZnO/CuO were biosynthesized by biological method and for the synthesis of the chitosan-ZnO/CuO nanoparticles film, the casting method was adopted. The product was analyzed by FTIR spectroscopy, X-ray diffraction (XRD), and Scanning Electron Microscope (SEM), respectively. The product of chitosan-ZnO/CuO nanoparticles film as paper disk and agar disk diffusion method was selected to study an antibacterial agent of this product. The Zn-O or Cu-O group was observed at a peak between 468-675 cm−1 for ZnO and 503 and 619 cm−1 for CuO nanoparticles, respectively. ZnO, CuO, and ZnO/CuO nanoparticles are in the crystalline form and it has a crystallite size of 13.21, 13.21, and 11.49 nm respectively. After interacting with chitosan, the metal nanoparticles such as ZnO, CuO, and ZnO/CuO nanoparticles can change the crystalline form of chitosan to be amorphous form. The addition of ZnO, CuO, and ZnO/CuO nanoparticles in the chitosan will change the surface morphology of chitosan. Chitosan-ZnO/CuO nanoparticles film can inhibit the growth of Escherichia coli bacteria.